Full text in PDF of the EDUCARE journal, issue of August 2014 - EDUCARE, Editor Journal (EDUCARE, 2014)
This journal was firstly published on August 17, 2008. Since issue of February 2009, the EDUCARE-IJES journal has been organized by the Lecturers of FKIP UMP (Faculty of Education and Teacher Training, Muhammadiyah University of Purwokerto) in Central Java; and published by Minda Masagi Press as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. The EDUCARE-IJES journal is published twice a year i.e. every August and February.